STRATEGIC PLANNING FOR CHANGE MANAGEMENT IN THE DIGITALIZATION OF BATIK PRINGMAS BASED ON THE MCKINSEY 7S FRAMEWORK - Farah Rihhadatul ‘Aisy; Adi Indrayanto; Siti Zulaikha Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Human resource management is a key driver of successful digital transformation in Micro, Small, and Medium Enterprises (MSMEs). Batik Pringmas, a traditional batik center in Banyumas Regency challenges in adopting digital marketing due to limited staff competencies, low digital literacy, and traditional management practices. This study aims to develop a change management strategy focused on strengthening human resources, using the McKinsey 7S Framework as an analytical tool. A descriptive qualitative method with a case study approach was employed, utilizing observation, semi-structured interviews, and document analysis. The findings reveal that successful digital transformation requires alignment across organizational elements, particularly in enhancing staff skills, adapting leadership styles, and fostering an adaptive work culture. This strategic design serves as an initial guide for Batik Pringmas in managing sustainable change through HR capacity building and aligned organizational values. Keywords: Digital Transformation; MSMEs; Change Management; McKinsey 7S; Human Resource Management